Translation Shift in English-Indonesian Subtitle of Green Book Movie - Simanjuntak, Rona Dewi Putri; Tangkas, I Wayan Dirgeyasa (Universitas Negeri Medan, 2022)
The purpose of this study is to find out 1) the types of category shifts that occur in the English-Indonesian subtitled Green Book film, and 2) the reasons for the translation shift in the English-Indonesian subtitled Green Book film. The data were analyzed by descriptive qualitative. The source of data in this research from subtitle english-indonesian subtitle of green book movie. The instrument for collecting data in this research is a documentary technique. the instrument of collecting data are used recorder and analyzed based on theory by Catford (1965). The results of the study show that 1) There are 303 data category shifts in the English-Indonesian subtitled Green Book film according to the results of the study. In total, there are four types of shifts: structure shift (24.8%), class shift (5.9%), unit shift (45.5%), and intra-system shift (which makes up the rest) (23.8%). The reason why the translation shift occurs in the green book movie subtitle is because of the textual equivalent. In translation shift, the shift occurs at the grammatical and lexical levels. Textual equivalent is a translation utterance between the source language and the target language. Some translations have no formal correspondence between the two language code systems. Shift the translation to achieve a good equivalence so that it can produce good and natural translation quality.